2013
DOI: 10.1002/jsfa.6154
|View full text |Cite
|
Sign up to set email alerts
|

Date fruit: chemical composition, nutritional and medicinal values, products

Abstract: Date fruit has served as a staple food in the Arab world for centuries. Worldwide production of date fruit has increased almost threefold over the last 40 years, reaching 7.68 million tons in 2010. Date fruit can provide many essential nutrients and potential health benefits to the consumer. Date fruit goes through four ripening stages named kimri, khalal, rutab and tamer. The main chemical components of date fruit include carbohydrates, dietary fibre, enzymes, protein, fat, minerals, vitamins, phenolic acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 108 publications
(271 reference statements)
10
101
2
1
Order By: Relevance
“…Concerning the mineral composition, our results are in great compatibility with those of many others studies which showed that dates fruits and seeds are a suitable source of minerals [15,17,22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Concerning the mineral composition, our results are in great compatibility with those of many others studies which showed that dates fruits and seeds are a suitable source of minerals [15,17,22].…”
Section: Discussionsupporting
confidence: 91%
“…In dates flesh, lipids are mainly concentrated in the skin, where they reach low values ranging from 0.1% to 0.9% [15]. Our results are similar to those from El Arem et al [7], who reported a fat content comprised between 0.2% and 0.5% but they are in contrast with those of Mohamed et al [18] for Sudanese date palms which ranged between 1.71% and 2.0%.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…특히 식물로부터 유래한 기능성 성분이 혈액순환 장 애, 고혈압, 고지혈증, 동맥경화, 뇌졸중, 중풍, 심장질환 등과 같은 여러 가지 병리학적 질환의 신호전달에 영향을 주는 것 으로 밝혀져 있다 [14]. 그 중에서 proanthocyanidin 및 anthocyanin과 같은 flavonoid 성분이 항산화 효능 뿐만 아니라 혈 액순환과 같은 다양한 신진대사의 활성화에 효능이 있는 것으 로 보고되고 있다 [25]. 이와 같이, 혈액순환 뿐만 아니라 복합 적인 질환의 효능을 나타내는 약용식물로 알려진 아사이베리 (Acai berry, Euterpe oleracea)는 아사이 야자나무의 열매이다.…”
Section: 서 론unclassified
“…The fruits are either consumed directly (fresh or in dried form) or are converted into products such as jam, wine, juice, vinegar, etc. [21]. However, DBs can be a better alternative to direct consumption of dates, especially during off-seasons.…”
Section: Introductionmentioning
confidence: 99%